Building analytic skills to drive improvements in patient care and organisational decision making. Issue 3 (6th July 2015) - Nick Harrop, Dr; Howard, Glen; Walker, Alex; Shaw, Dominick E; Hatton, James
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper briefly outlines a development programme designed to improve the skills of NHS Information Analysts and assesses the extent these skills have been developed. There are significant opportunities for the NHS to utilise information more effectively, and Analysts have a key role. However, training opportunities prior to the development of this programme have been limited for this professional group. The purpose of this paper is to explore the potential benefits to the organisations, patients and the NHS as a whole, that improvements in the quality of analysis can deliver. Design/methodology/approach – The authors compared pre-course and post-course self-assessment of skill levels of Analysts who attended the programme. The authors also considered general feedback and comments from participants. Findings – All of the 40 skills areas assessed demonstrated an increase in mean competency score. In cohorts 1 and 2, 38 of these were statistically significant (p < 0.001-0.041, mean increase in score 1.0). For cohorts 3-5, 37 were statistically significant (p < 0.001-0.012; mean increase 1.2). These findings were supported by the positive feedback from participants. Practical implications – The programme develops skills for NHS Information Analysts which can improve the quality of analysis in the NHS, offering significant potential to improve the effectiveness and efficiency of healthcare. Originality/value – The Information Analysts' Development Programme provides the only training programme available for NHS Information Analysts, contributing to the development of data driven service improvement within the NHS. This may harness the power contained within data to drive improvement and ensure patients receive the highest quality of care.